Review of 1997 Guidance Note on Governance : A Proposed Framework for Enhanced Fund Engagement. (Policy Papers; Policy Paper ;, 2018)
This paper proposes the adoption of a framework that would supplement the 1997 Fund's Guidance Note on the Role of the Fund in Governance Issues, adopted by the Executive Board (the '1997 Governance Policy'). While the 1997 Governance Policy remains an appropriate basis for the Fund's work in this area, further guidance from the Executive Board is needed to ensure that the objectives of that policy are achieved. Experience over the past 20 years has underscored the critical impact that governance issues can have on the Fund's work. In particular, there is evidence that corruption can have a pernicious effect on a country's ability to achieve sustainable, inclusive economic growth. As requested by the Executive Board, the proposed Framework for Enhanced Engagement by the Fund ('Framework for Enhanced Fund Engagement') is designed to promote more systematic, effective, and candid engagement with member countries regarding those governance vulnerabilities, including corruption, that are judged to be macroeconomically critical. Perhaps most importantly, the application of the Framework for Enhanced Fund Engagement to all members on a systematic basis will enhance evenhandedness. Finally, the Framework is designed to strengthen the global fight against corruption by promoting governmental measures that prevent private actors from offering bribes or providing services that enable the proceeds of corrupt acts to be concealed, particularly in the transnational context.